Isolation and characterization of Acanthamoeba spp. from air-conditioners in Kuala Lumpur, Malaysia - Chan, L.L.; Mak, J.W.; Low, Y.T.; Koh, T.T.; Ithoi, I.; Mohamed, S.M. (2011)
During a study on the quality of the indoor environment, Acanthamoeba spp. were detected in 20 out of 87 dust samples collected from air-conditioners installed in a four-story campus building located in Kuala Lumpur, Malaysia. Twenty-one cloned Acanthamoeba isolates designated as IMU1 to IMU21 were established from the positive primary cultures. Five species were identified from the 16 isolates according to the morphological criteria of Pussard and Pons; i.e. A. castellanii, A. culbertsoni, A. griffini, A. hatchetti and A. polyphaga. Species identities for the remaining five isolates (IMU4, IMU5, IMU15, IMU20 and IMU21), however, could not be determined morphologically. At genotypic characterization, these isolates were placed into T3 (IMU14); 15 (IMU16 and IMU17)and T4 (all the remaining isolates). To predict the potential pathogenicity of these Acanthamoeba isolates, thermo- and osmotolerance tests were employed; many isolates were predicted as potential human pathogens based on the outcome of these tests. This is the first time potentially pathogenic Acanthamoeba have been isolated from air-conditioners in Malaysia. (C) 2010 Elsevier B.V. All rights reserved.